Dissolved Organic and Inorganic Carbon Flow Paths in an Amazonian Transitional Forest - Neu, Vania; Ward, Nicholas D.; Krusche, Alex V.; Neill, Christopher (Frontiers in Marine Science, 2016)
As a raindrop falls from the atmosphere, over vegetation and forest canopies, and enters soils and streams it experiences a dynamic exchange of carbon constituents with the surrounding environment. Understanding the magnitude and dynamics of carbon export in above and below ground flow paths is critical for constraining the influence of terrestrial and aquatic ecosystems on global carbon cycling. Here we examine the concentration and flux of dissolved organic and inorganic carbon (DOC and DIC) in rainfall, throughfall, stemflow, overland flow, soil solution, groundwater, and stream water in an Amazonian transitional forest located near the arc of deforestation. Rainfall was enriched in DOC by interactions with atmospheric particles derived from both biogenic and anthropogenic emissions, resulting in a flux of 82.3 kg C ha-1 yr-1, which was the largest flux from each respective flow path. Forest throughfall, stemflow, and direct overland flow mobilized DOC from products of terrestrial primary production and decomposition. Net throughfall represented the second largest DOC flux (68.4 kg C ha-1 yr-1), whereas stemflow and overland flow only had a flux of 1.5 and 3.9 kg C ha-1 yr-1, respectively. Much of the DOC in above ground flow paths was removed from solution as the rain percolated through soil layers due to both biological decomposition and sorption/desorption to mineral surfaces, resulting in low concentrations in stream and groundwater (2.6 ± 2.4 mg L-1 and 1.45 ± 0.3 mg L-1, respectively) relative to throughfall (43.9 ± 5.2 mg L-1) and stemflow (30.6 ± 2.7 mg L-1). The flux of DIC in each respective flow path was generally lower than for DOC, and likely driven by atmospheric gas exchange and inputs from respiration and decomposition. DOC concentrations in above ground flow paths were highest during the first rainfall after a dry period, whereas DIC concentrations generally increased throughout the rainy season as soil moisture increased.